2018
DOI: 10.1088/1361-6528/aab009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of radiation tolerance in GaAs/AlGaAs core–shell and InP nanowires

Abstract: Radiation effects on semiconductor nanowires (NWs) have attracted the attention of the research community due to their potential applications in space and atomic fields. The effective implementation of NW devices in a radiation environment is a matter of concern. Here, the photoluminescence (PL) and time-resolved PL (TRPL) measurements were performed on both GaAs and InP NWs at room temperature before and after 1 MeV H irradiation with fluences ranging from 1 × 10 to 5 × 10 p cm. It is found that the degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Afterward, Li et al carried out 1 MeV proton and H + irradiation experiments on GaAs/AlGaAs core-shell NWs at room temperature and found that the minority carrier lifetime is closely related to the irradiation-induced defect density by photoluminescence (PL) method. In addition, the size dependence of the carrier lifetime damage factor of GaAs NWs is mainly attributed to a special dynamic mechanism of defect annihilation, as summarized by them [14,15]. These results generally indicate that NW is a better candidate structure for radiation resistance.…”
Section: Introductionmentioning
confidence: 93%
“…Afterward, Li et al carried out 1 MeV proton and H + irradiation experiments on GaAs/AlGaAs core-shell NWs at room temperature and found that the minority carrier lifetime is closely related to the irradiation-induced defect density by photoluminescence (PL) method. In addition, the size dependence of the carrier lifetime damage factor of GaAs NWs is mainly attributed to a special dynamic mechanism of defect annihilation, as summarized by them [14,15]. These results generally indicate that NW is a better candidate structure for radiation resistance.…”
Section: Introductionmentioning
confidence: 93%
“…The degradation of PL intensity and the decreasing lifetime of the minority carriers are closely related to the concentration of defects produced by proton irradiation. [ 203,218,219 ] The pre and post‐effect on the parameters (such as absolute short circuit current density ( J sc ), open‐circuit voltage ( V oc )) of 800 nm, and 80 nm cells of GaAs as a function of 3 MeV p + of various fluence was studied in Figure 17b. The reduction in V oc as a function of proton fluence is affected by the increase in the current, [ 203 ] which can be described by the following two diode model equations: [ 220 ] Jbadbreak=J01exp[q(VJRnormals)kT1]goodbreak+J02exp[q(VJRnormals)n2kT1]goodbreak+VJRsRshunt\[J = {J_{01}}{\exp ^{\left[ {\frac{{q\left( {V - J{R_{\rm{s}}}} \right)}}{{kT}} - 1} \right]}} + {J_{02}}{\exp ^{\left[ {\frac{{q\left( {V - J{R_{\rm{s}}}} \right)}}{{{n_2}kT}} - 1} \right]}} + \frac{{V - J{R_{\rm{s}}}}}{{{R_{{\rm{shunt}}}}}}\] where q is the charge of the electron, k is Boltzmann's constant, T is the temperature, V is the bias voltage of the device, and R s and R shunt are series and shunt resistances, respectively.…”
Section: Radiation Effect On Thin Films Transistor (Tft)mentioning
confidence: 99%
“…[204] The 800 nm cell exhibits significant degradation in J sc as a function of proton irradiation fluence with a slight increase in Reproduced with permission. [203] Copyright 2018, IOP. b,c) IV characteristics and EQE of the 800 and 80 nm cells before and after various proton irradiation fluence of GaAs.…”
Section: (19 Of 34)mentioning
confidence: 99%
See 2 more Smart Citations